2023
DOI: 10.3389/fnmol.2023.1156674
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ERK/CREB pathway in pain and analgesia

Abstract: Research has long centered on the pathophysiology of pain. The Transient Receiver Potential (TRP) protein family is well known for its function in the pathophysiology of pain, and extensive study has been done in this area. One of the significant mechanisms of pain etiology and analgesia that lacks a systematic synthesis and review is the ERK/CREB (Extracellular Signal-Regulated Kinase/CAMP Response Element Binding Protein) pathway. The ERK/CREB pathway-targeting analgesics may also cause a variety of adverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Previous study showed that CDH12 regulates neurite outgrowth through activation of CREB 25 . CREB has also been reported as a downstream effector of ERK 26 . Transcription factor enrichment analysis revealed that CREB binding sites were enriched in the promoter regions of genes upregulated in ADR-ZsGreen + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous study showed that CDH12 regulates neurite outgrowth through activation of CREB 25 . CREB has also been reported as a downstream effector of ERK 26 . Transcription factor enrichment analysis revealed that CREB binding sites were enriched in the promoter regions of genes upregulated in ADR-ZsGreen + cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, mutations of R94A or K114A significantly impeded the reduction of ERK induced by Imperatorin treatment, suggested that Imperatorin certainly possible binds to ERK to inhibit its expression and activation. Recent studies have indicated that ERK phosphorylates CREB at Ser133, a crucial modification for CREB‐mediated transcriptional effects closely linked to various physiological processes, including gene expression, cognitive learning ability, oxidative stress, and neuroinflammation 49–51 . We next explored the association between ERK and CREB in the infection system, and demonstrated that ERK interacted with CREB in HBV infected cell model.…”
Section: Discussionmentioning
confidence: 97%
“…to various physiological processes, including gene expression, cognitive learning ability, oxidative stress, and neuroinflammation. [49][50][51] We next explored the association between ERK and CREB in the infection system, and demonstrated that ERK interacted with CREB in HBV infected cell model. Crucially, we observed that Imperatorin markedly inhibited the interaction between ERK and CREB.…”
Section: Conflict Of Interests Statementmentioning
confidence: 99%
“…Similar explanation was shown in Li’s study [ 12 ], they revealed that the downstream targets of BDNF-TrkB signaling including p-ERK, p-CREB, and p-Akt, which were pivotal to neuroinflammation, neuronal survival. In Zhen’s study in 2023 [ 53 ], they believed ERK/CREB pathway was essential for oxidative stress and neuroinflammatory processes. In brief, based on previous studies, we speculate BDNF might mediate NLRP3 activation through activating ERK-CREB or PI3K-AKT-CREB signaling pathway (Fig.…”
Section: Discussionmentioning
confidence: 99%